A framework for knowledge reuse in product design and development process. (1st January 2013) - Benmiled, Achraf; Bakhouya, Mohamed
In this paper, a framework for knowledge reuse during product design and development is introduced. The framework exploits the capitalised knowledge in the best way and proves most relevant for users in order to facilitate their tasks. It offers the relevant knowledge to the right person by taking into account the roles of the involved persons and their collaborations throughout the product design process. The framework is supported by a software tool that brings an automatic help to users via a personalised search for knowledge in order to facilitate their tasks. Experiments are performed and results are presented to show the effectiveness of reusing knowledge during product development lifecycle.